2001
DOI: 10.1038/sj.onc.1204764
|View full text |Cite
|
Sign up to set email alerts
|

Cellular proteins localized at and interacting within ND10/PML nuclear bodies/PODs suggest functions of a nuclear depot

Abstract: ND10, PML bodies or PODs have become the de®ning nuclear structure for a highly complex protein complement involved in cell activities such as aging, apoptosis, the cell cycle, stress response, hormone signaling, transcriptional regulation and development. ND10 are present in many but not all cell types and are not essential for cell survival. Here, we review the cellular proteins found in ND10, their few known interactions and their contribution to the ND10 structure per se and to functions elsewhere in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
181
0
3

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(187 citation statements)
references
References 87 publications
3
181
0
3
Order By: Relevance
“…The major components of PML-NBs are promyelocytic leukemia protein (PML) and Sp100, and the proapoptotic adaptor protein Daxx plays a crucial role in the assembly of PML-NBs by connecting sumoylated PML and Sp100. [9][10][11] These provide a scaffold to harbor several prominent regulatory factors including tumor suppressors, transcriptional regulators, and enzymes for signal transduction, and thereby PML-NBs contribute to multiple mechanisms of cellular control. 8,10,[12][13][14][15][16] While the functional interactions of these components remain unclear, the architecture of PML-NBs seems to be particularly important since its abrogation caused by a chromosomal translocation t(15;17) results in acute promyelocytic leukemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major components of PML-NBs are promyelocytic leukemia protein (PML) and Sp100, and the proapoptotic adaptor protein Daxx plays a crucial role in the assembly of PML-NBs by connecting sumoylated PML and Sp100. [9][10][11] These provide a scaffold to harbor several prominent regulatory factors including tumor suppressors, transcriptional regulators, and enzymes for signal transduction, and thereby PML-NBs contribute to multiple mechanisms of cellular control. 8,10,[12][13][14][15][16] While the functional interactions of these components remain unclear, the architecture of PML-NBs seems to be particularly important since its abrogation caused by a chromosomal translocation t(15;17) results in acute promyelocytic leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] These provide a scaffold to harbor several prominent regulatory factors including tumor suppressors, transcriptional regulators, and enzymes for signal transduction, and thereby PML-NBs contribute to multiple mechanisms of cellular control. 8,10,[12][13][14][15][16] While the functional interactions of these components remain unclear, the architecture of PML-NBs seems to be particularly important since its abrogation caused by a chromosomal translocation t(15;17) results in acute promyelocytic leukemia. 8,14,16 In contrast, forced expression of PML, as well as the expression of oncogenic Ras, induces apparent hyperplasis (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, both proteins, PML and hDaxx, are components of a cellular subnuclear structure known as nuclear domain 10 (ND10) or PML nuclear bodies. ND10 structures represent multiprotein complexes of the cellular proteins PML, hDaxx, and Sp100 that assemble in distinct foci within the interchromosomal space of the nucleus (42). Previous studies identified the PML protein as the defining factor of ND10 structures since it functions as a kind of scaffold protein that is responsible for the assembly and maintenance of this domain and recruits other ND10-associated proteins like hDaxx to this subnuclear structure (25,53).…”
mentioning
confidence: 99%
“…Whereas Cajal bodies are often found associated to several different small nuclear RNA and small nucleolar RNA gene loci as well as histone gene loci (1)(2)(3)(4)(5), PML bodies are frequently located in the MHC gene region (6). For both nuclear bodies, different types of movements were described and assigned to distinct subgroups of Cajal and PML bodies (7)(8)(9)(10)(11)(12). The analysis of a baby hamster kidney cell line revealed that a fraction of PML bodies moved over longer distances and in an energy-dependent manner.…”
mentioning
confidence: 99%